An Experimental Study of Bond Behavior of Micro Steel Fibers Added Self-compacting Concrete with Steel Reinforcement - Salam, Abdul; Room, Shah; Iqbal, Shahid; Mahmood, Khalid; Iqbal, Qaiser (Periodica Polytechnica Civil Engineering, 2020)
The obstruction offered by the surrounding concrete to the pulling out of embedded steel bar is known as bond strength. Steel fibers addition to concrete improves its bond strength by arresting the cracks due to their bridging effect. Bond failure occurs when cracks in the surrounding concrete initiates, providing enough space for bar to be pulled-out. Micro steel fibers efficiently control the formation of micro cracks and may improve bond strength to a greater extent compared to the longer steel fibers. However, it reduces the workability of concrete which is of greater importance in case of self-compacting concrete (SCC). Reduction of workability is less pronounced when straight micro steel fibers are used due to their shorter lengths and straight geometry. Thus, different amount of straight micro steel fibers (0.25 %, 0.5 %, 0.75 %) were incorporated in to SCC to investigate their fresh and mechanical properties with major emphasis on the bond strength. Results indicate that steel fibers addition to SCC improve the splitting tensile strength and bond strength significantly with a maximum increase of 33.5 % and 54.9 % respectively with 0.75 % fibers addition. An equation is proposed for the calculation of bond strength with micro steel fibers addition to SCC with a maximum variation of 4 % to those of experimental values.